(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2013)
Nowadays, consumer behaviouris influenced not only by consumer personalities and motivations, but also by the relationships within families. Family is a social group and it can be considered the cornerstone of consumers so it has a crucial place in the perception of marketing. Marketeers closely interested in this issue to know the family which changed and renewed in course of time. It provides a tremendous advantage for a marketeer to know the family structure and its consumption characteristics ( Durmaz and Zengin, 2011: 53). In this study, the affect of cultural factors on consumer buying behaviour is investigated. A survey was conducted on 1400 people from the different parts of Turkey. The information acquired from the results are analyzed and interpreted by the computer packet programs. Turkey has seven regions. From each region two provinces are selected by random sampling method. A face to face survey was conducted on 100 people from each province and in total 1400 people participated in the survey. The information obtained from the results are analyzed and interpreted by the computer packet programs.